Comparative Analysis of Risk-Based Decision-Making Theory and Value-Based Decision-Making Theory in UMKM Business - Afita, Rina; Pasaribu, Veta Lidya Delimah (Indonesian Journal of Entrepreneurship and Startups, 2025)
Business decisions are used to determine business activities both in the short term and long term. In UMKM businesses, business decisions are very important because business decisions affect the sustainability of the company, profitability, recruitment success, and professional attitudes in business. To help UMKM determine the right approach to decision making based on their needs and conditions, this study was conducted by comparing the theory of risk-based decision making and the theory of value-based decision making. The research method used is the literature study method and data analysis from the application of both approaches. The results of the study show that the risk-based approach is related to risk management, therefore it can help UMKM actors in identifying, measuring, and managing possible risks so that decision making is more structured and based on probability analysis. Value-based decision making is related to business ethics; therefore, it can help MSMEs in determining the long-term benefits and values generated by the company such as corporate image, employee and consumer loyalty. The conclusion of this study is that these two theories when applied simultaneously will provide optimal results because they can achieve a balance between risk mitigation and the creation of sustainable business value